Bioactivity of Engineered Nanoparticles - Yan, Bing; Zhou, Hongyu; Gardea-Torresdey, Jorge L. (Nanomedicine and Nanotoxicology,, 2017)
This book brings together reviews from international experts who are exploring the biological activities of nanomaterials for medical applications or to better understand nanotoxicity. Topics include but are not limited to the following: 1) mechanistic understanding of nanostructure-bioactivity relationships; 2) the regulation of nanoparticles' bioactivity by means of chemical modification; 3) the new methodologies and standard methods used to assess nanoparticles' bioactivity; 4) the mechanisms involved in nanoparticle-biomolecule interactions and nanoparticle-cell interactions; and 5) biomedical applications of nanotechnology. The book will be a valuable resource for a broad readership in various subfields of chemical science, engineering, biology, environment, and medicine.